On the Physiology of Normal Swallowing as Revealed by Magnetic Resonance Imaging in Real Time - Arno Olthoff; Shuo Zhang; Renate Schweizer; Jens Frahm (Gastroenterology Research and Practice)
The aim of this study was to assess the physiology of normal swallowing using recent advances in real-time magnetic resonance imaging (MRI). Therefore ten young healthy subjects underwent real-time MRI and flexible endoscopic evaluations of swallowing (FEES) with thickened pineapple juice as oral contrast bolus. MRI movies were recorded in sagittal, coronal, and axial orientations during successive swallows at about 25 frames per second. Intermeasurement variation was analyzed and comparisons between real-time MRI and FEES were performed. Twelve distinct swallowing events could be quantified by real-time MRI (start time, end time, and duration). These included five valve functions: oro-velar opening, velo-pharyngeal closure, glottal closure, epiglottic retroflexion, and esophageal opening; three bolus transports: oro-velar transit, pharyngeal delay, pharyngeal transit; and four additional events: laryngeal ascent, laryngeal descent, vallecular, and piriform sinus filling and pharyngeal constriction. Repetitive measurements confirmed the general reliability of the MRI method with only two significant differences for the start times of the velo-pharyngeal closure (t(8)=-2.4, P≤0.046) and laryngeal ascent (t(8)=-2.6, P≤0.031). The duration of the velo-pharyngeal closure was significantly longer in real-time MRI compared to FEES (t(8)=-3.3, P≤0.011). Real-time MRI emerges as a simple, robust, and reliable tool for obtaining comprehensive functional and anatomical information about the swallowing process.